Social Support in the Prevention of Mother to Child Transmission to HIV Infected Mother - Lusa Rochmawati; Os. Hartanto; Soewarto; Diffah Hanim (Proceeding of International Conference on Science, Health, And Technology, 2019)
HIV-AIDS epidemic is a global problem that is increasing every year. Along with the increasing number of men who have sex unsafe, causing an increase in the number of women infected with HIV. Programs the Prevention of Mother to Child Transmission (PMTCT) is an effective intervention to prevent HIV transmission from mother to child. One of the efforts of the Prevention of Mother to Child Transmission (PMTCT), is psychological support, social and health care, then, to HIV-infected mothers and babies and their families. The purpose of this research to know the description of social support in the the Prevention of Mother to Child Transmission (PMTCT) to HIV-infected mothers. This type of research is qualitative with phenomenological approach in the form of case studies. Subjects were HIV-infected mothers amounted to one person. Data collection techniques with participatory observation, interview and documentation field. The research instrument uses an interview guide. Triangulation of data sources for data accuracy, and analyzed by an interactive model. Result: the subject get of social support from husband, peers, support NGOs, and health workers in health care facilities. Social support provided in the form of emotional support, facilities and infrastructure, information and peer support. The impact of social support from the aspect of psychological, health and social environment. Conclusion: In general, the subject get of social support in prevention of mother to child transmission well.